Variation in the behaviour of an obligate corallivore is influenced by resource availability - Gunn, Rachel L.; Hartley, Ian R.; Algar, Adam C.; Nadiarti, N.; Keith, Sally A. (Behavioral ecology and sociobiology, 2022)
Marine environments are subject to increasing disturbance events, and coral reef ecosystems are particularly vulnerable. During periods of environmental change, organisms respond initially through rapid behavioural modifications. Whilst mean population level modifications to behaviour are well documented, how these shifts vary between individuals, and the relative trade-offs that are induced, are unknown. We test whether the frequency and time invested in different behaviours varies both between and within individuals with varying resource availability. To do this, we quantify differences in four key behavioural categories (aggression, exploration, feeding and sociability) at two sites of different resource availability, using an obligate corallivore butterflyfish species ( Chaetodon lunulatus ). Individuals on a low resource site held larger territories, investing more time in exploration, which was traded off with less time invested on aggression, feeding and sociability. Repeatability measures indicated that behavioural differences between sites could plausibly be driven by both plasticity of behaviour within individuals and habitat patchiness within feeding territories. By combining population-level means, co-correlation of different behaviours and individual-level analyses, we reveal potential mechanisms behind behavioural variation in C. lunulatus due to differences in resource availability. Significance statement Using observational methods, we identify differences in the behaviour of an obligate corallivorous butterflyfish ( Chaetodon lunulatus ) between a high and a low resource site. We use a combination of density surveys, territory mapping and behavioural observation methods in a comparative analysis to relate behaviour directly to the environment in which it occurs. Bringing together insights from game theory and optimal foraging, we also use our results to highlight how understanding the correlations of different behaviours can inform our understanding of the extent to which behaviours are plastic or fixed. Furthermore, by considering how multiple behaviours are correlated, we move away from exploring individual behaviours in isolation and provide an in-depth insight into how differences in behaviour both between individuals and at the population level can affect responses to declining resource availability.